Pengaruh Konten Media Sosial Instagram @musclefirstofficial dan Brand Ambassador terhadap Minat Beli Suplemen pada Followers Muscle First, - Fitrah Nur Islamiah; Edy Prihantoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of Instagram social media content @musclefirstofficial and brand ambassadors on interest in buying supplements among Muscle First followers. Social media, especially Instagram, has become an effective marketing tool in building brand awareness and improving consumer purchasing decisions. This study uses a quantitative approach with an explanatory method, where data is collected through questionnaires to respondents who are followers of the @musclefirstofficial account. The analysis results show that social media content has a significant influence on consumer buying interest, especially through visual elements such as photos, videos and interesting captions. Apart from that, brand ambassadors also play an important role in increasing purchasing interest, with visibility and credibility factors as the main elements that influence purchasing decisions. Simultaneously, social media content and brand ambassadors contributed 65.7% to interest in purchasing Muscle First supplements. These findings indicate that a social media-based marketing strategy combined with selecting the right brand ambassador can increase product attractiveness and encourage consumer purchasing decisions.